2015
DOI: 10.1128/jvi.03176-14
|View full text |Cite
|
Sign up to set email alerts
|

Nanobody Binding to a Conserved Epitope Promotes Norovirus Particle Disassembly

Abstract: Human noroviruses are icosahedral single-stranded RNA viruses. The capsid protein is divided into shell (S) and protruding (P) domains, which are connected by a flexible hinge region. There are numerous genetically and antigenically distinct noroviruses, and the dominant strains evolve every other year. Vaccine and antiviral development is hampered by the difficulties in growing human norovirus in cell culture and the continually evolving strains. Here, we show the X-ray crystal structures of human norovirus P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 41 publications
6
90
0
Order By: Relevance
“…A single crystal of GII.10 P domain Nano-85/Nano-26 double complex diffracted to 2.3Å in C121 space group. Binding epitopes and interactions of both Nanobodies were identical to those in the individual complexes [31]. Nano-26 bound at the bottom of the P domain, perpendicular to Nano-85 binding site ( Fig 7A).…”
Section: Structure Of Gii17 P Domain Nano-4 Complexmentioning
confidence: 75%
See 4 more Smart Citations
“…A single crystal of GII.10 P domain Nano-85/Nano-26 double complex diffracted to 2.3Å in C121 space group. Binding epitopes and interactions of both Nanobodies were identical to those in the individual complexes [31]. Nano-26 bound at the bottom of the P domain, perpendicular to Nano-85 binding site ( Fig 7A).…”
Section: Structure Of Gii17 P Domain Nano-4 Complexmentioning
confidence: 75%
“…Moreover, the structural analysis could offer insights into vulnerable regions on the capsid that could be targeted by inhibitors. Indeed, we recently discovered that a human norovirus specific Nanobody (termed Nano-85) bound to intact norovirus VLPs and the Nanobody binding interaction caused the VLPs to disassemble [31]. Our results suggested that the Nano-85 binding epitope might represent a vulnerable region on the capsid that is important for the structural integrity.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations